ANALISIS KESALAHAN PENULISAN SITASI DAN DAFTAR PUSTAKA PADA LAPORAN PENELITIAN TINDAKAN KELAS - Febbi Imelliya; Aisyah Az Zahra; Najwa Dinar Nur Dzakiyah; Riska Yulianti; Imron Fauzi (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2026)
The writing of academic papers must adhere to proper citation practices and the correct formatting of the reference list. This is important to acknowledge the work of others and avoid plagiarism. However, many students still make errors in citing sources and compiling reference lists. This study aims to analyze common errors in reference list formatting and assess the degree to which the formatting complies with current citation guidelines. The method used is a Systematic Literature Review (SLR). Data were obtained from various sources, such as books, journals, and previous studies published within the last 10 years, and then analyzed. The results of the study indicate that common errors include improper formatting, incomplete source information, and inconsistent citation styles. This study is expected to enhance understanding of citation and reference list writing, thereby contributing to improved quality in academic works, particularly Classroom Action Research reports.